Pitfalls in Sterilization: The Core Role of Nursing - Wafaa Ahmed Al-Musalam1, Ahmed Ibrahim Al Abdi2, Hajar Abdullah Bubshait3, Manal Abdullah Alhassan4, Fatimah Yousef Alhamood4, Ramlah Hejji Mohammed Albrahim4, Zahra Abdulhadi Al Hmood4, Essra Essam K Alzayer5; Mohammed Abdulazdhim A Alsharfa6, Hussain Ali Aleid7, Omnia Abbas Al Abdrabalnabi8, Hussain Mohammad Al Ribh9, Ali Abdullal Al Afeef 6, Mousa Mohammed Albesher10; Ali Hussain A Al Basher11, Hilalah Ali Saad Albardweel4,Abdulkareem Abdullah Abdullah Alsubi 4, Mahdi Abdulkareem Abdullah Alsubi12, Noura Ali Ban Maan4. (International Journal of Scientific Research and Innovative Studies, 2024)
Sterilization is a critical process in healthcare settings, ensuring that medical instruments and environments are free from harmful microorganisms. However, despite stringent protocols, various pitfalls in sterilization practices can compromise patient safety and healthcare outcomes. Nurses play a pivotal role in the sterilization process, from overseeing the correct application of sterilization techniques to educating and training healthcare staff. This review examines common pitfalls in sterilization, including equipment failure, human error, and improper adherence to protocols. It also explores the core responsibilities of nurses in mitigating these risks and ensuring the highest standards of infection control. Through continuous education, vigilant monitoring, and adherence to best practices, nurses can significantly reduce the incidence of sterilization-related infections and enhance overall patient care. Keywords: Pitfalls, Sterilization, Nursing. Received Date: April 20, 2024 Accepted Date: May 20, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/171 DOI: https://doi.org/10.5281/zenodo.13118788